Adjuvant treatment of coronary heart disease angina pectoris with Chinese patent medicine: A prospective clinical cohort study. Issue 33 (August 2019) - Liu, Yijia; Li, Zhu; Shen, Dandan; Song, Yanqi; Huang, Mengnan; Xue, Xiaoxue; Xie, Jing; Jiao, Ziyi; Gao, Shuming; Xu, Yilan; Gao, Shan; Wang, Xianliang; et al.
Abstract: Background: Patients with coronary heart disease (CHD) angina pectoris are in critical condition, which can cause sudden death, myocardial infarction, and other adverse events, and bring serious burden to families and society. Timely treatment should be given to improve the condition. Western medicine treatment of angina pectoris failed to meet the demand of angina symptom control. Objective: It is hoped that the research method with higher evidential value will be adopted to compare the short-term, medium-term, and long-term effects of Chinese patent medicine combined with conventional western medicine and conventional western medicine alone in the treatment of CHD angina pectoris, so as to tap the clinical efficacy advantages of traditional Chinese medicine (TCM) and provide reliable data support for its clinical application. Methods: A prospective cohort study was conducted among patients with CHD angina pectoris who were treated with oral Chinese patent medicine and conventional western medicine. The patients were divided into exposed group and nonexposed group according to whether or not the patients with CHD angina pectoris were treated with Chinese patent medicine. The exposed group was treated with TCM combined with conventional western medicine, while the nonexposed group was treated with conventional western medicine alone. Patients need to be hospitalized for 2 weeks as the introduction period and whether to enter the group is determined according to the treatment and medication conditions of the patients. The follow-up time points were 0th, 4th, 12th, 24th, and 48th weeks. The main events and secondary events were used as the evaluation criteria for clinical efficacy of CHD angina pectoris. In the experimental study, we will use strict indicators to detect standard operation procedure for multinomics and bacterial flora detection. Conclusion: This study will provide evidence for the clinical efficacy advantages of Chinese patent medicine and reliable support for its clinical application through test data.